Analisis Peran Orang Tua Terhadap Motivasi Belajar Siswa Kelas V SD Negeri Kalicari 01 Semarang Di Masa Pandemi Covid-19 - Nanda Danty Kumalasari; Henry Januar Saputra; Diana Endah Handayani (STKIP Andi Matappa Pangkep, 2022)
This study aims to describe the role of parents in the learning motivation of V SD Negeri Kalicari 01 Semarang during the Covid-19 pandemic. This type of research uses a qualitative approach. Sources of data in this study were classroom teachers, parents, and students. The data analysis technique used is the Miles and Huberman Analysis Interactive model. The results showed that the role of parents in the learning motivation of fifth graders at SD Negeri Kalicari 01 Semarang during the Covid-19 pandemic had been going well, it was known from observations made by parents in distributing questionnaires. The role of parents on student learning motivation is to educate, guide, accompany, motivate children to learn well. Based on the results of the research and discussion, it was concluded that the role of parents on the learning motivation of fifth graders at SD Negeri Kalicari 01 Semarang has been carried out well by parents and students.